B-hadron production at the LHC from bottom-quark pair production at NNLO+PS - Javier Mazzitelli; Alessandro Ratti; Marius Wiesemann; Giulia Zanderighi (Physics Letters B, 2023)
The production of B hadrons is among the most abundant fundamental QCD processes measured at the LHC. We present for the first time predictions for this process accurate to next-to-next-to-leading order in QCD perturbation theory by simulating bottom-quark pair production at this accuracy matched to parton showers. Our novel results are in good agreement with experimental data for the production of different types of B hadrons from ATLAS, CMS and LHCb at 7 TeV and/or 13 TeV, including various fiducial cross sections as well as single- and double-differential distributions, and 13 TeV/7 TeV cross-section ratios.